1994
DOI: 10.1099/13500872-140-9-2315
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic diversity of fluorescent pseudomonads isolated from field-grown sugar beet

Abstract: A sample of 30 fluorescent pseudomonads isolated from the phyllosphere of sugar beet throughout a single growing season and shown to be closely related on the basis of fatty acid methyl ester (FAME) analysis was subjected to detailed phenotypic and genotypic characterization. Phenotypic traits were assessed on the basis of biochemical properties, assimilation of sole carbon sources, FAME analysis, organic pyrolysate content (MS-pyrolysis), and total cellular protein profiles. With the exception of total cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 9 publications
4
46
0
Order By: Relevance
“…However, many of the same and similar reports state that gene exchanges between clusters may also explain some of their results (9,27,29,30), implying less than total congruence between genotypic (rDNA) and phenotypic (nutritional) data. Many studies of Pseudomonas have presented genotypic and phenotypic data and commented on their congruence (15,18,34,39), but few have rigorously tested such congruence. Our results, rigorously showing no congruence, suggest that statements of congruence should be based on careful tests of this issue and that the famous metabolic versatility of the genus might well be founded in large measure on the easy ability to acquire opportunistic metabolic capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the same and similar reports state that gene exchanges between clusters may also explain some of their results (9,27,29,30), implying less than total congruence between genotypic (rDNA) and phenotypic (nutritional) data. Many studies of Pseudomonas have presented genotypic and phenotypic data and commented on their congruence (15,18,34,39), but few have rigorously tested such congruence. Our results, rigorously showing no congruence, suggest that statements of congruence should be based on careful tests of this issue and that the famous metabolic versatility of the genus might well be founded in large measure on the easy ability to acquire opportunistic metabolic capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of phenotypes is also reflected at the genetic level, and evidence is mounting to suggest that the diversity of genome architecture (of both chromosomes and accessory genetic elements) is of particular significance. Fingerprinting studies performed by many workers have revealed a remarkable degree of restriction fragment polymorphism among strains of a speciesand even among strains that are closely related on phenotypic grounds (see, for example, Ginard et al, 1997 ;Grothues et al, 1988 ;Rainey et al, 1994). Genome sizes vary widely, ranging from 3n7 Mbp for Pseudomonas stutzeri (Ginard et al, 1997) to 7n1 Mbp for Pseudomonas aeruginosa (Schmidt et al, 1996), with the genome sizes of Pseudomonas fluorescens SBW25, Pseudomonas syringae pv.…”
Section: The Diversitymentioning
confidence: 99%
“…Others have shown that analyses of fatty acid methyl ester (FAME) profiles (Abel e t al., 1962;Kaneda, 1968;Lambert e t al., 1983;DeBoer & Sasser, 1986;Vaisanen e t al., 1991 ;Chase e t al., 1992;Rainey e t al., 1994), DNA patterns in pulsed-field gel electrophoresis (Carlson e t al., 1994;Rainey et al, 1994), RAPDs (Welsh & McClelland, 1990;Mazurier et al, 1992;Wang et al, 1993;Andersen e t al., 1996), 16s rRNA gene sequences (Stackebrandt & Charfreitag, 1990;Ash e t al., 1991a, b;Stackebrandt e t al., 1991 ;Aquino de Muro e t al., 1992), and PCR products with primers based on characterized genes (Gustafson, 1992;Darrasse e t al., 1994;Leite e t al., 1994;Schraft & Griffiths, 1995) have all provided phylogenetic information about members of the B. cereus group or other bacteria. We focused on the methods that we expected to have the greatest power to distinguish bacterial strains within a species.…”
Section: -0951 0 1996sgmmentioning
confidence: 99%